Sustainable Development in Social, Economic and Cultural Context to Answer Global Challenges to Improve Community Welfare in Indonesia - Sabri, Sabri; Febrianti, Eka; Asnah, Asnah; Sari, Rika Novita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Management is a series of processes that include planning, organizing, directing, and controlling activities to achieve organizational goals in an effective and efficient manner, using the resources owned by the organization. In modern development management, information technology is added as a tool to facilitate the operation of the development system to improve the welfare of society, especially in Indonesia. The implementation of development management that needs special attention, both at the national and regional government levels, includes the preparation of regional development plan documents, implementation of performance evaluations, monitoring regional development, and management of regional development management information systems. The purpose of this study is to see how development in the social, economic, and cultural contexts meets the needs of society and to examine what are the main concepts of development that are relevant to answering global and local challenges. This research method uses reference studies. From the results of this study it was found that development in the social, economic, and cultural contexts has a very significant role in meeting the needs of society, and the main concept of development that is relevant to answering global and local challenges is the concept of sustainable development.